Different domains of the murine RNA polymerase I-specific termination factor mTTF-I serve distinct functions in transcription termination. - Evers, R (1995)
Termination of mouse ribosomal gene transcription by RNA polymerase I (Pol I) requires the specific interaction of a DNA binding protein, mTTF-I, with an 18 bp sequence element located downstream of the rRNA coding region. Here we describe the molecular cloning and functional characterization of the cDNA encoding this transcription termination factor. Recombinant mTTF-I binds specifically to the murine terminator elements and terminates Pol I transcription in a reconstituted in vitro system. Deletion analysis has defined a modular structure of mTTF-I comprising a dispensable N-terminal half, a large C-terminal DNA binding region and an internal domain which is required for transcription termination. Significantly, the C-terminal region of mTTF-I reveals striking homology to the DNA binding domains of the proto-oncogene c-Myb and the yeast transcription factor Reb1p. Site-directed mutagenesis of one of the tryptophan residues that is conserved in the homology region of c-Myb, Reb1p and mTTF-I abolishes specific DNA binding, a finding which underscores the functional relevance of these residues in DNA-protein interactions.